No pharmacokinetic interactions between candesartan and amlodipine following multiple oral administrations in healthy subjects - Kim, Jung-Ryul (Drug Des Devel Ther, 2018)
PURPOSE: To evaluate the pharmacokinetics and pharmacodynamics of candesartan and amlodipine in the absence and presence of each other in healthy subjects. METHODS: This study consisted of two parts: part 1, the effect of amlodipine on candesartan; part 2, the effect of candesartan on amlodipine. Each part was designed as a randomized, open-label, two-sequence, two-period, two-intervention crossover study with 20 subjects and performed separately in different populations. Pharmacokinetic assessments were performed over 48 hours for candesartan in part 1 and 72 hours for amlodipine in part 2 after drug administration on Day 10. Safety data included the results of physical examinations, clinical laboratory tests, vital signs, an electrocardiogram, and adverse events. RESULTS: For both candesartan and amlodipine, the 90% confidence intervals for the geometric mean ratios of area under the concentration-time curve from time zero to the time of dosing interval of 24 hours and maximum concentration after drug administration fell within the bioequivalence acceptance criteria. Although this study was conducted in normotensive subjects, blood pressure lowering effects were observed in all intervention groups and co-administration of candesartan and amlodipine reduced blood pressure more than amlodipine alone, but similar to candesartan alone. No serious adverse event was reported throughout the study, and all treatment emergent adverse events were mild to moderate in severity and were recovered without sequelae. CONCLUSION: Co-administration of candesartan and amlodipine did not change the systemic exposure of each drug alone in healthy subjects. The administration of candesartan 32 mg alone, amlodipine 10 mg alone, and co-administration of candesartan and amlodipine were well tolerated during the study.